Pengembangan Pendidikan Agama dan Al-Qur'an dalam Pondok Ramadhan di SDN Bulukerto 2 Magetan - Suparman, Yogi; Al Fudiah, Nurul; Aisy, Nurul; Mansoor, Jihan Nur Hidayah (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2024)
Religious Education and the Qur'an in the Ramadhan Huts at SDN Bulukerto 2 Magetan is one of the initiatives for the development of religious education carried out in the elementary school environment. This program was carried out by Team VI of the Real Work Lecture (KKN) of STIQ Zad Cianjur and the teacher council of SDN Bulukerto 2 Magetan in the month of Ramadan, with the aim of increasing religious understanding and love for the Qur'an among children. Pondok Ramadhan activities include learning to read and write the Qur'an, tadabbur and tafsir of the Qur'an, as well as providing material and practices for the implementation of daily worship such as fasting, ablution and prayer. The results of these activities show an increase in children's religious understanding and worship practice and make a positive contribution in the formation of spiritual values at primary school age. The Pondok Ramadhan program at SDN Bulukerto 2 Magetan provides an example of how religious education can be effectively integrated in the formal school curriculum to strengthen children's character and religious education.